Soil Amendments for Immobilization of Potentially Toxic Elements in Contaminated Soils: A Critical Review - Nourren Sajjad; Hamda Rafique; Muhammad Bilal; Muhammad Shahbaz; Muhammad Azeem; Muhammad Ahsan (Dialogue Social Science Review (DSSR), 2025)
Soil pollution by potentially toxic elements (PTEs) has several detrimental environmental effects. This review emphasizes the element type, soil and amendment, immobilization efficiency and mechanisms, field applicability, etc. Immobilization Technique Soil Amendments Several soil amendments have been used worldwide as retardants of PTEs. Out of these amendments, biochar has been the most favored in recent years because of its unique improved surface properties. The application of suitable amendments in combination is also advisable to maximize efficiency. The physical and chemical processes these amendments employ to reduce PTEs’ soil bioavailability include precipitation, complexation, reduction and oxidation, ion exchange, and electrostatic forces. However, such soil properties as initial soil pH, clay content, sesquioxides, organic matter content, and processes such as sorption/desorption and redox highly govern the immobilizing effectiveness of the amendments for PTEs in soils. The capability of immobilizing agents may lead to the development of low-cost yet efficient remedial applications that adhere to green and sustainable remediation concepts. Analyzing the expenses and the sustainability of the solutions is very important before their application as it guarantees the proper and caring approach to the environment.